Combined hydrodynamic and control analysis on optimal kinematic parameters for bio-inspired autonomous underwater vehicle manoeuvring - Wright, Marvin; Xiao, Qing; Zhu, Qiang (Frontiers in Physics, 2023)
To investigate the manoeuvring performance of a body-caudal fin robot fish, a numerical framework combining computational fluid dynamics and multi-body dynamics with a closed-loop control algorithm was established in this study. Within this framework, we modelled a body-caudal fin swimmer as a multi-body system with the shape of a NACA0012 hydrofoil. The manoeuvring performance was investigated by using different curvature magnitudes and distributions along the centre line (the curvature is defined by means of a curvature envelop function as part of the general body undulation equation). To characterize the turning performance, a new parameter named cost of manoeuvring (CoM) is proposed. This parameter provides a combined assessment of the turning radius, linear and angular velocity components, and power. It is found that when the body curvature is introduced, the swimmer switches from straight-line swimming to quasi-steady turning at a constant speed. Further investigations were conducted to study contributions of head and tail deformations on the turning performance by comparing predominantly head and tail curved envelopes. Results reveal that a tail-dominated envelope improves performance, whereas a head-dominated envelope has a negative effect.